Peranan Kepemimpinan Kepala Sekolah untuk Mewujudkan Kualitas Lulusan yang Unggul dalam Kompetensi Religius di MIM Kahuman Klaten - Muhammad Iqbal Nashrulloh; Ravi Dwi Ramandhika (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Research intends to reveal the role of principals in fostering the quality of graduates who excel in religious competence through various activities managed by the principal. The research used is a type of qualitative research with data collection techniques in the form of unstructured direct interviews with the principal. The results of this study explain that the principal plays an important role, especially in carrying out his role as an educator, manager, administrator, supervisor, leader, innovator and motivator. The principal also plays an important role in managing the school so that the expected goals can be achieved by paying attention to teacher performance and teacher competence in carrying out their duties, especially in fostering the quality of students who excel in religious competence.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//